The transfer and maximisation of dry-land strength & power into in-water thrust in competitive swimming - Tan, Quah Jian (2019)
BACKGROUND: The ability of competitive swimmers to maximise dry-land strength gains into useful swimming thrust is important for swimming performance. Findings were equivocal regarding the transference of dry-land strength into swimming thrust. The appropriate test modalities to monitor such transference were not explored. This study investigated the relationship between dry-land shoulder internal rotation (SIRt) strength and swimming thrust across swimmers of different competitive levels. To the author’s knowledge, no similar studies comparing SIRt strength and swimming thrust were conducted using the gold-standard equipment for both dry-land and in-water testing. AIM: To compare SIRt strength to swimming thrust between swimmers of varying competitive level at different swim speeds. HYPOTHESIS: i) Positive association of SIRt power and front-crawl swimming power within each competitive level; ii) Stronger association of SIRt power and front-crawl swimming power as competitive level increases. METHODS: 10 competitive swimmers (4 Elite, 6 Non-Elite) performed concentric SIRt on the Biodex at 90°/s and 180°/s. Participants also completed a 25-m swim using the Aquanex Analysis System at slow, moderate and all-out pace with the front-crawl stroke. RESULTS: Significant correlation (p < 0.05) were found between dry-land power and in-water swimming power at all three swim speeds. There are also promising trends indicating that elite swimmers have better transference of dry-land strength into in-water thrust. CONCLUSION: The elite swimmers may be more efficient in their swimming performance than non-elite swimmers due to better technique. However, more studies regarding such transference in swimming is warranted to shed more light into this area.